MEASUREMENT OF THE PERFORMANCE AND ACCOUNTABILITY OF ZAKÄ€H ORGANIZATIONS IN YOGYAKARTA - Wirawan Hardinto; Sigit Handoyo; Mahdalena Toha (IAIN Surakarta, 2018)
This study aimed to investigate the influence of spirituality, internal control, and organization commitment toward Zakāh organization performance and internal control toward accountability in Zakāh organizations. The population of the study is the staff of BAZ and LAZ in Province of DI Yogyakarta who has a minimum position at the middle manager. There are 16 of 28 BAZ and LAZ in Province of DI Yogyakarta which participated in this research. The number of the sample was 63 respondents. All data of the respective measurement items are tested with reliability and validity test based on Alpha Cronbach to the internal consistency by using SPSS program version 15 and to analyze the structural equation model by using PLS (Partial Least Square). The model of the relationship between five variables is shown that internal control has positive effects on accountability. Accountability has a positive relation with Zakāh organization performance. Internal control has a positive relation with Zakāh organization performance. Meanwhile, organization commitment does not influence on Zakāh organization performance. Spirituality has a positive relation to Zakāh organization performance.